Controversies on the treatment strategy for rectal submucosal cancer: Case series and review of the literature. (25th April 2013) - Chan, Shannon Melissa; Chiu, Philip Wai Yan; Hon, Sok Fei; Lo, Anthony Wing Ip; Ng, Simon Siu Man
Abstract : Endoscopic submucosal dissection (SD) has emerged as one of the treatment strategies for submucosal rectal cancers. The present study reviewed the clinical outcomes of patients with rectal submucosal cancer treated by ESD. This was a retrospective review of four patients who had rectal tumor treated by ESD from 2010 to 2012 with histopathology showing T1 submucosal adenocarcinoma. The mean age (SD) was 69.5 (7.33) and the male to female ratio was 3:1. There were no post‐ESD complications. The mean (SD) size of the tumors was 2.93 (0.87) cm. One patient with deep resection margin involvement received laparoscopic low anterior resection. Another with deep margin involvement of <1 mm refused surgery and was treated by chemoradiotherapy.There was no recurrence in all the cases with a mean follow‐up duration of 461.3 (209.0) days. ESD was one of the important treatment strategies for T1sm‐s rectal cancer especially when the risk of nodal metastasis was low. ESD spared the patient from colostomy when the T1 cancer was located in the lower third of the rectum. The role of adjuvant and neoadjuvant chemoradiotherapy remains controversial.